An association study between DLGAP1 rs11081062 and EFNA5 rs26728 polymorphisms with obsessive–compulsive disorder in a Chinese Han population - Li J (Dove Medical Press, 2015)
Jiang Li,1 Jiajia Cui,2 Xiuhai Wang,3 Jianhua Ma,4 Haitao Niu,4 Xu Ma,5–7 Xinhua Zhang,2,4 Shiguo Liu8 1Physiatry Department, The Affiliated Hospital of Qingdao University, 2Department of Psychiatry, 3Department of Genetics, Medical College, Qingdao University, 4The Affiliated Hospital of Qingdao University, Qingdao, People’s Republic of China; 5Graduate School, Peking Union Medical College, 6National Research Institute for Family Planning, 7World Health Organization Collaborating Centre for Research in Human Reproduction, Beijing, People’s Republic of China; 8Prenatal Diagnosis Center, The Affiliated Hospital of Qingdao University, Qingdao, People’s Republic of China Background: A recent genome-wide association study indicated that the single nucleotide polymorphisms (SNPs) rs11081062 in DLGAP1 and rs26728 in EFNA5 were associated with obsessive–compulsive disorder (OCD) in Caucasians. The present case–control association study assessed the global relevance of these two SNPs with respect to OCD subtypes in a Chinese Han population. Methods: We recruited 320 OCD patients and 431 age- and sex-matched controls from a Chinese Han population. rs11081062 and rs26728 SNPs were genotyped by real-time TaqMan polymerase chain reaction, and the chi-squared test was used to compare allele and genotype frequencies of variants between the two groups. Results: No significant differences were found in allele or genotype frequencies of DLGAP1 rs11081062 and EFNA5 rs26728 between the OCD and control groups. Moreover, consistently negative results were observed when classifying by sex, onset age, and comorbidity. However, on analyzing OCD subphenotypes, significant associations were observed between rs11081062 and the presence of contamination obsessions and cleaning compulsions (χ2=7.724, P=0.021 by genotype; χ2=3.745, P=0.053 by allele; and χ2=0.821, P=0.365 by genotype, χ2=27.809, P=0.000 by allele, respectively), and rs26728 with the presence of repeating compulsions (χ2=8.285, P=0.004 by genotype; χ2=7.512, P=0.006 by allele). Conclusion: Although we found no association between DLGAP1 rs11081062 and EFNA5 rs26728 SNPs with OCD in a Chinese Han population, obvious associations were observed with OCD subphenotypes. Therefore, it appears to be useful to divide OCD into more homogeneous subphenotypes to help understand the complex genetic basis of this disorder. Further investigations are needed to replicate these findings using larger sample sizes, different populations, and other polymorphisms. Keywords: DLGAP1, EFNA5, obsessive-compulsive disorder, polymorphism